Study of the aetiology of wheezing illness at age 16 in two national British birth cohorts. Issue 7 (July 1996) - Lewis, S.; Butland, B.; Strachan, D.; Bynner, J.; Richards, D.; Butler, N.; Britton, J.
Abstract : BACKGROUND: Data from two national British birth cohorts were used to measure the increase in prevalence of wheezing illness at age 16 between 1974 and 1986, and to investigate the role of several potential risk factors in the increase. METHODS: The occurrence of self-reported asthma or wheezy bronchitis within the past year, and the frequency of attacks of wheezing illness at age 16, were compared in 11, 262 and 9266 children born in one week of 1958 and 1970, respectively. The effects of several putative risk factors for asthma–including birth weight, maternal age, birth order, breast feeding, maternal smoking in pregnancy, child's personal smoking, and father's social class–on the change in occurrence of wheezing illness at age 16 were assessed by multiple logistic regression. RESULTS: The annual period prevalence of asthma or wheezy bronchitis at age 16 increased from 3.8% in 1974 to 6.5% in 1986 (prevalence ratio (PR) = 1.71, 95% CI 1.52 to 1.93). The proportion of children experiencing attacks more than once a week increased from 0.2% to 0.7% (PR = 3.77, 95% CI 2.28 to 6.23). The prevalence of self-reported eczema and hayfever within the past year doubled between 1974 and 1986, suggesting that the increase in asthma was part of a general increase in the prevalence of atopic disease. However, in the complete dataset, after adjustment for the effects of the risk factors studied, the prevalence odds ratio for asthma or wheezy bronchitis in 1986 compared with 1974 was virtually unchanged from the unadjusted value at 1.77 (95% CI 1.46 to 2.15). CONCLUSION: The prevalence of wheezing illness in British teenagers increased by approximately 70% between 1974 and 1986. This increase appears to have occurred in the context of a general increase in atopic disease and was largely unexplained by changes in the distribution of maternal age, birth order, birth weight, infant feeding, maternal smoking, active smoking by the child, or father's social class.